Efficacy and safety of parecoxib and flurbiprofen axetil for perioperative analgesia in children: a network meta-analysis - Chen, Xi; Chen, Pan; Chen, Xiao; Huang, Min; Tang, Kejing; He, Qiuyi (Frontiers in Medicine, 2023)
Objective The aim of this study was to systematically review the efficacy and safety of parecoxib and flurbiprofen axetil for perioperative analgesia in children through Bayesian network meta-analysis. Methods We systematically searched PubMed, Embase, Cochrane Library, Web of Science, Sinomed, CNKI, VIP, and Wanfang Data databases on 18 July 2022 to obtain randomized controlled trials comparing perioperative parecoxib or flurbiprofen with placebo or standard treatment for pediatric analgesia. The outcomes were the postoperative pain score and the incidence of adverse events. The Gemtc package of R-4.0.3 and Stata 17.0 were used for Bayesian network meta-analysis. Results We retrieved 942 articles and 49 randomized controlled trials involving 3,657 patients who met the inclusion criteria. Compared with children who received placebo treatment, those who received flurbiprofen axetil had lower pain sores at each time point within 24 h postoperatively, and those who received parecoxib had lower pain sores at each time point within 12 h postoperatively. Compared with children who received tramadol treatment, both the children who received flurbiprofen axetil or parecoxib had lower pain scores at 8 h postoperatively. The ranking results demonstrated that flurbiprofen axetil had significant superiority in reducing pain scores at 2, 4, and 12 h postoperatively, and parecoxib had significant superiority in reducing pain scores at 0, 0.5, 1, 6, 8, and 24 h postoperatively. In terms of safety, compared with children who received placebo, those who received flurbiprofen axetil or parecoxib had a lower incidence of total adverse events and postoperative agitation. Compared with tramadol, flurbiprofen axetil and parecoxib both significantly reduced the incidence of total adverse events and postoperative nausea and vomiting. Compared with flurbiprofen axetil or fentanyl, parecoxib significantly reduced the incidence of postoperative nausea and vomiting. The ranking results showed that parecoxib was advantageous in decreasing the incidence of total adverse events and postoperative nausea and vomiting. Conclusion Flurbiprofen axetil was most effective at reducing pain scores at 2, 4, and 12 h postoperatively. Parecoxib had an advantage in terms of reducing pain scores at 0, 0.5, 1, 6, 8, and 24 h postoperatively, as well as the incidence of total adverse events and postoperative nausea and vomiting. Systematic trial registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=348886, PROSPERO (CRD42022348886).